Rashba effect on linear and nonlinear optical properties of a cylindrical core/shell heterojunction quantum dot - Kria, M.; Nautiyal, Vijit V.; Lakaal, K.; El Hamdaoui, J.; Pérez, L. M.; Varsha,; Laroze, D.; Prasad, V.; Long, G.; Feddi, E. (Frontiers in Physics, 2022)
The Rashba effect may play an important role in the nonlinear optical properties of heterojunction quantum dots. In this work, we have theoretically examined the effects of Rashba spin-orbit interaction on an electron in a cylindrical core/shell quantum dot. The modifications of various properties of cylindrical core/shell quantum dots, such as transition energies, dipole transition matrix elements, and linear and non-linear optical properties due to changes in Rashba coupling parameter, magnetic field, and effective Rydberg energy were studied. We solved the Schr\"odinger equation using numerical methods and obtained energy eigenvalues as functions of the aforementioned parameters. It was observed that the magnetic field has a considerable effect on the absorption coefficients and refractive index. It was also observed that increasing the magnetic field shifts the resonances toward higher energies. Additionally, when the Rashba coupling coefficient is increases, there is an increment in the absorption coefficient and the refractive index, as well. Our results demonstrated that we can manipulate the optical properties of cylindrical core/shell quantum dots using an external magnetic field.